2019
DOI: 10.1177/0145561319840571
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Features of Papillary Carcinoma in the Second Branchial Cleft Cyst

Abstract: Clinically, it may be very difficult to differentiate between benign branchial cleft cyst (BCC) and malignant BCC with papillary carcinoma preoperatively. Radiological features were reviewed retrospectively between benign BCC and malignant BCC with papillary carcinoma using computed tomography (CT) and magnetic resonance (MR) images. All patients had only a mass on the right upper lateral neck without lesion in the thyroid gland. Two patients had a mass in the upper medial part of BCC on CT images and one pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Sagit et al reviewed the literature in 2013 and found only 11 cases including their own [4]. In 2019, Hong et al, reported additional three cases [5]. Up to the present time, a total of 15 cases in the literature including the present case were summarized in Table 1.…”
Section: Discussionmentioning
confidence: 76%
“…Sagit et al reviewed the literature in 2013 and found only 11 cases including their own [4]. In 2019, Hong et al, reported additional three cases [5]. Up to the present time, a total of 15 cases in the literature including the present case were summarized in Table 1.…”
Section: Discussionmentioning
confidence: 76%